A Mathematical Model for Carbothermic Reduction of Dust-Carbon Composite Agglomerates - Kuwauchi. Y.; M. Barati (Canadian Institute of Mining, Metallurgy and Petroleum, 2011)
Recycling of dust using a rotary hearth furnace (RHF) has gained considerable attention in the past two decades for the sustainable production of steel with less environmental impact. In order to further promote the recycling of electric arc furnace dust and carbonaceous wastes using the RHF process, a mathematical model was developed to predict the reaction behaviour of dust-reductant composites. The reduction kinetics of zinc and iron oxides as well as the volatilization behaviour of volatile matter in the reluctant were considered. The modeling approach and some preliminary results are presented in this article.